2021
DOI: 10.3389/fpsyt.2021.703180
|View full text |Cite
|
Sign up to set email alerts
|

The Transition From Maternity Blues to Full-Blown Perinatal Depression: Results From a Longitudinal Study

Abstract: Background: The aims of the present study are to: (1) assess the frequency of maternity blues (MB); (2) identify the clinical and social characteristics more frequently associated with the onset of depressive symptoms after delivery; and (3) verify the hypothesis that the presence of maternity blues is a risk factor for the onset of a full-blown depressive episode in the 12 months after delivery.Methods: This is a longitudinal observational study. All pregnant women who gave birth at the inpatient unit of Gyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
1
13
1
1
Order By: Relevance
“…Our work, like others before it, emphasizes the importance of personal and family psychiatric history and obstetrical factors in the postpartum blues [1, 4, 69, 13]. We found a close association between personal psychiatric history and postpartum blues, specifically with a history of major depressive episode and anxiety disorders, confirmed after multivariate analysis, which are also found as associated factors by several studies.…”
Section: Discussionsupporting
confidence: 86%
“…Our work, like others before it, emphasizes the importance of personal and family psychiatric history and obstetrical factors in the postpartum blues [1, 4, 69, 13]. We found a close association between personal psychiatric history and postpartum blues, specifically with a history of major depressive episode and anxiety disorders, confirmed after multivariate analysis, which are also found as associated factors by several studies.…”
Section: Discussionsupporting
confidence: 86%
“…In their network meta-analysis, Sun et al (2021) [ 33 ] reported that women with emergency CS have a significantly increased risk of postpartum depression compared with women with vaginal delivery (43 studies, OR:1.53 [95%CI 1.22 to 1.91]). Luciano et al (2021) [ 34 ] reported that women with maternity blues had an increased risk of increased Edinburgh Postnatal Depression Scale score (OR: 7.79, 95%CI: 6.88 to 8.70). Gerli et al (2021) [ 14 ] also reported that CS was a predictor of maternity blues.…”
Section: Discussionmentioning
confidence: 99%
“…People experiencing Antenatal Depression have frequently reported other stressors including conflict with family/partner, risk for miscarriage, and financial difficulties while pregnant ( 11 ). Additionally, a recent study found that the presence of maternal blues, which can present between 1 to 10 weeks postpartum, has a significant relationship to higher depressive symptomology scores and the development of depression and/or anxiety disorder ( 12 , 13 ). Since antenatal mental health problems are often overlooked and represent such a great opportunity for interventions, we want to identify state specific policy levers to improve perinatal mental health.…”
Section: Introductionmentioning
confidence: 99%